Focus Group Discussion (FGD) dan Implementasi Teknologi Informasi untuk Analisis Jabatan di Lingkungan Yayasan Pendidikan - Rahayuningsih, Tri; Sembiring, Lala Septiyani; Armalita, Rani; Anip, Anip Febtriko (Lembaga Dongan Dosen, 2024)
Job analysis is an important step in human resource management to describe the responsibilities, authorities, and competencies in each job position. The rapidly growing Education Foundation, with the addition of new core businesses to diversify revenue, faces challenges in adjusting its organizational structure. New positions, such as the Business and Innovation Unit, require effective coordination with other work units to maintain the foundation's vision. The main problem is the mapping of positions and career levels from contract employees to permanent employees, as well as adjusting the functions of teachers serving in the foundation. Evaluation of the HR management system is also needed to ensure sustainable performance and employee satisfaction. This program uses a Focus Group Discussion (FGD) approach to involve stakeholders in identifying needs and developing relevant implementation steps with 65 participants. The use of information technology is applied to support job analysis, improve efficiency, accuracy, and data-based decision making. The results of this program include increased participant understanding of the importance of information technology-based job analysis, as well as the preparation of an organizational structure that is in accordance with new needs. This program is expected to contribute to the professionalization of HR management at the Education Foundation, support business innovation, and ensure employee satisfaction.